The Influence of Green Awareness and Green Perceived Value on Green Purchase Intention at Coffee Shops in DKI Jakarta with Green Trust as a Mediating Variable in the Perspective of Sustainable Business - Syahputra, Ozzamma; Shiratina, Aldina (ARE Publisher, 2026)
Objectives: This study aims to analyze the influence of green awareness and green perceived value on green purchase intention among coffee shop consumers in DKI Jakarta, while exploring the mediating role of green trust.Methodology: A descriptive quantitative approach was employed, involving 200 respondents selected through probability sampling using a cluster sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) based on Smart-PLS to test the hypotheses and mediating effects.Finding: The results indicate that green awareness and green perceived value have a positive and significant impact on both green purchase intention and green trust. Furthermore, green trust significantly influences green purchase intention and effectively mediates the relationship between green awareness and green perceived value toward consumers' purchase intentions.Conclusion: These findings underscore that green trust is a pivotal factor in strengthening green purchase intention. Consequently, coffee shop businesses in DKI Jakarta are advised to consistently enhance education and communication regarding eco-friendly practices to solidify consumer trust and intention to purchase green products.